Expression of N-CAM-180 and N-Cadherin during development in two southamerican anuran species (Bufo arenarum and Hyla nana) - VH Casco; A Peralta Soler; MF Izaguirre (European Journal of Histochemistry, 2009)
Cadherins and N-CAM are Ca++-dependent and Ca++-independent cell adhesion molecules respectively. These molecules play a key role in morphogenesis and histogenesis. We determined the spatiotemporal pattern of N-cadherin and N-CAM-180 kDa expression by immunohistochemistry during development in two South-American anuran species (Bufo arenarum, toad and Hyla nana, frog). Both N-cadherin and N-CAM were not detectable during early developmental stages. Expression of Ncadherin appeared between the inner and the outer ectoderm layers at stages 19-20. At stages 24 -25, Ncadherin was expressed in the neural tube and the heart. In early tadpoles, N-cadherin expression increased along with the central nervous system (CNS) morphogenesis, and reached its maximum level at metamorphic climax stage. N-Cadherin expression was not uniformly distributed. At stage 42, olfactory placodes and retina expressed N-cadherin. Contrary to N-CAM, the strongly myelinated cranial nerves were not labeled. N-Cadherin was present in several mesoderm derivatives such as the notochord, heart and skeletal muscle. The non-neural ectoderm and the endoderm were always negative. Expression of N-CAM appeared first in the neural tube at stages 24-25 and the level of expression became uniform from pre-metamorphic to metamorphic climax tadpoles. At this latter stage, a clear N-CAM immunolabeling appeared in the nerve terminals of pharynx and heart. N-Cadherin and N-CAM were found mainly co-expressed in the CNS from early tadpole to metamorphic climax tadpole. Our results show that the expression of N-CAM and N-cadherin is evolutionary conserved. Their increased expression during late developmental stages suggests that N-CAM and N-cadherin are involved in cell contact stabilization during tissue formation.